Disparities and Parallels in Internationalization: The Ethiopian Experience - Tamrat, Wondwosen; Teferra, Damtew (International Higher Education, 2018)
This article examines the ways in which internationalization is expressed in developed and developing countries. Specifically, we discuss factors such as motives, approaches, policies, strategies, and the nature of institutional relationships in the Ethiopian context.